In vitro fertilization cycle and embryo transfer outcomes in oligoanovulatory patients with hypothalamic hypogonadism vs. polycystic ovary syndrome and compared with normo-ovulatory patients - Rebecca A. Heidenberg, B.S; Elizabeth S. Ginsburg, M.D; Catherine E. Gordon, M.D; Andrea Lanes, Ph.D (Elsevier, 2022)
Objective: To study the difference in the live birth rates between anovulatory women with hypothalamic hypogonadism (HH) and those with polycystic ovary syndrome (PCOS) and normo-ovulatory women undergoing fresh embryo transfer or frozen embryo transfer (FET). Design: Retrospective cohort study. Setting: Academic medical center. Patient(s): Patients with oligoanovulation (HH, n = 47; PCOS, n = 533) and normo-ovulation (tubal factor infertility, n = 399) undergoing in vitro fertilization and intracytoplasmic sperm injection cycles from January 1, 2012, to June 30, 2019. Intervention(s): None. Main Outcome Measure(s): Live birth rate. Result(s): Patients with HH had longer stimulation durations than both patients with PCOS and tubal factor infertility. Patients with HH had fewer oocytes retrieved than patients with PCOS, but their numbers of blastocysts were similar. Patients with HH and tubal factor infertility had similar numbers of oocytes retrieved and blastocysts. In fresh embryo transfer cycles, the live birth rates were similar among patients with HH, PCOS, and tubal factor infertility (37.5% vs. 37.1% vs. 29.3%, respectively). When evaluating FET cycles, patients with HH had lower live birth rates than patients with PCOS (26.5% vs. 46.7%) and tubal factor infertility (42.6%). Conclusion(s): Live birth rates are similar among patients with HH, PCOS, and normo-ovulation undergoing fresh embryo transfer but are significantly lower in women with HH undergoing FET.